Regio-and stereoselective C(sp2)-H acylation of enamides with aldehydes : via transition-metal-free photoredox catalysis - Zhao, Kai (2022)
A straightforward and efficient C(sp2)-H acylation of enamides with aldehydes via transition-metal-free photoredox catalysis is demonstrated. The transformation proceeded smoothly without resorting to expensive and potentially toxic iridium or ruthenium polypyridyl-based photocatalysts under mild conditions, furnishing a diverse range of synthetically crucial, geometrically defined β-acylated enamides in a stereoselective and regioselective manner. This journal is